Design Thinking Approach in Sustainable Development Planning - Muhammad Insan Kamil; Yogi Suprayogi Sugandhi; Budiman Rusli; Slamet Usman Ismanto (Aliansi, 2022)
This paper aims to find out how applying a design thinking approach in collaborative planning can overcome urban problems. The design thinking approach to collaborative planning in the city of Bandung received appreciation at The XIth Annual Meeting of the UNESCO Creative Cities Network as a best practice in completing the SDGs agenda, making cities and settlements inclusive, safe, resilient, and sustainable. However, the collaborative planning product did not continue to impact, and the approach no longer received support from the local government. Previous studies on applying the design thinking approach to urban planning have primarily focused on the relationship between actors and are considered unable to provide the application of design thinking in the development planning process at the government level. We use data from the implementation of design action, development planning deliberations, and legislative recess for the preparation of annual work plans that are described using qualitative methods to gain an in-depth understanding of the application of design thinking in 3 phases of collaborative planning (a) problem identification, (b) problem modeling, and (c) problem-solving. Our research shows that applying a design thinking approach to collaborative planning is more acceptable to stakeholders. However, without political support and formal integration into the development planning system, this approach cannot maintain the sustainability of development.